Ответы и объяснения

2013-07-18T01:29:13+04:00
Поупрощаем левую часть и доведем ее до результата в правой:
(sin\ a\ cos\ b+sin\ b\ cos\ a)^2 + (cos\ a\ cos\ b+sin\ a\ sin\ b)^2=\\\ =(sin^2a\ cos^2b+sin^2b\ cos^2a+2sin\ a\ cos\ b\ cos\ a\ 
sin\ b)+\\\ 
+(cos^2a\ cos^2b+sin^2a\ sin^2b+2sin\ a\ cos\ a\ sin\ b\ 
cos\ b)-\\\ - 4sin\ a\ sin\ b\ cos\ a\ cos\ b=\\\ 
=sin^2a\ cos^2b+sin^2a\ sin^2b+sin^2b\ cos^2a+cos^2a\ cos^2b=\\\ =sin^2a\ (cos^2b+sin^2b)+cos^2a\ (cos^2b+sin^2b)=\\\ = sin^2a+cos^2a=1.
Тождество доказано.